Usability analysis using webuse method in Bisma Informatika certification registration system - Kadek Dwi Pradnyani Novianti; I Wayan Oka Sukardiyasa; I Putu Dodit Setiawan (Compiler, 2021)
Bisma Informatika is one of the educational institutions with Diploma education level in Denpasar that serves certification services for people who want to take certification expertise, especially those engaged in Information and Computer Technology. In order to serve optimally, Bisma Informatika applies registration which can be done by the computerized system so that the participant's data can be stored properly. After observing the use of the system at the time of participant registration, an initial conclusion can be drawn that many data fields cannot be understood by the user so they must ask the officer on duty. The data fields in question such as the choice of certification class are not clear because it does not include the implementation time, the unaccompanied participants who come from the common line (so can not include the student identification numbers), telephone numbers that cannot be entered if they exceed the capacity of the permitted number, and inconsistent field filling instructions. This shows that the usability aspect of the registration system is not being considered properly. This study evaluates the interface design and features of the Bisma Informatika certification registration system by considering the context and user needs. In an effort to find out the context and user needs, a Website Usability Evaluation (WEBUSE) questionnaire was used. The results of the WEBUSE questionnaire showed that the four categories which have a good usability level, only content, organization and readability categories are obtained.